Linguistic, Structural and Rhetorical Analysis of Surah “Al-kāfirūn” in the Qur’an - Kairbekov, N.E. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
This article analyses the 109 Surah of Qur’an (Q 109) from linguistic and religious studies points of view. The Surah “al-Kāfirūn”, despite its rather short length, serves as a quite useful source for contextual analysis of the time of its formation. Unfortunately, this Surah has never been a central focus of academic attention. Using communicative methods of word-by-word translations, the research reveals the complex nature of relationships between early Islamic community and other religious groups — Jews and Christians. Considering Q 109 in its historical context, the article demonstrates how Muslims, being a minority group at that time, attempted to negotiate its own existence with other religious groups. The research is therefore divided into two dimensions of analysis: micro-level where intra-structure of Q 109 is analyzed and macro-level where intertextual coherence with other Surahs is scrutinized. The authors argue that by studying Surah 109 in the context of other Surahs, it is possible to gain a deeper understanding of the Qur'an as a whole, and the role that this chapter played in the development of early Islamic community. Therefore, this article provides a comprehensive analysis of Surah 109 of the Qur'an, drawing on both linguistic and religious studies perspectives. Through its examination of the historical context in which the Surah was revealed, its analysis of its content, and its examination of its inter-textual coherence within the Qur'an, the authors aim to shed new light on this important and under-studied chapter of the Qur'an.
Құрандағы «Əл-Кафирун» сүресін лингвистикалық құрылымдық жəне риторикалық талдау
Лингвистический, структурный и риторический анализ суры «Аль-Кафирун» в Коране
Keywords: surah; Quran; Islam; religions; al-kafirun; Muhammad; Christianity; linguistics; disbelievers; text